Does Debts Foster Economic Growth?: The Experience of Malaysia - Lau, Evan; Choong, Chee-Keong; Liew, VK; Puah, Chin-Hong (Academic Journals, 2010)
The study examines the effect of different types of debts on the economic growth in Malaysia during the sample period 1970 - 2006. Using cointegration test, the findings suggest that all components of debts have a negative effect on long-run economic growth. In addition, the Granger causality test reveals the existence of a short-run causality linkage between all debt measures and economic growth in the shortrun. The policy conclusion is that an increase in foreign debt level adversely influences economic performance, whereas the decline in the rate of economic growth weakens the ability of the country to service its debt.